Penyelamatan Air Tanah dan Penanggulangan Sampah Melalui Program Biopori dan Komposter di Pemukiman Kecil Kelurahan Ciputat dan Ciputat Timur - Eka Permanasari; Feby Hendola; Rahma Purisari; Ratna Safitri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
The growth of middle class in Indonesia has raised the number of houses being built in cities like Depok, Bogor, Bekasi Tangerang. Big real estates have emerged in these supporting cities along with the mushroomed numbers of small clusters adjacent to them. Stand on 3000-5000 m2 land, these clusters have limited public facilities such as proper sanitation, water catchment, and waste management. The water catchment area have reduced significantly which causes deficit ground water supply during the dry season. Another problem is the households waste left unsorted and directly sent to the garbage collector have made the number of solid waste piling up in the dumping site. This research analyzes three small clusters which locations are adjacent to Bintaro Jaya housing estate. This program focus in three programs: (a. Changing people’s mindset in handling the household waste by choosing the right products (front strategy), sort the waste, and treat the organic waste (rear strategy); (b) Installing minimum 2 biopores on every house and open areas; (c) Making composter to transform household waste into compost. Through FGD and social intervention, this research has encouraged community to change their behavior towards biopore and composter program installed in three small clusters in Bintaro.